Residual effects of different green manures on the growth and yield of wheat - Hoque, Tahsina Sharmin; Akter, Farhana; Islam, Md Rafiqul (Asian Journal of Medical and Biological Research, 2017)
Green manures can enrich soils with organic matter and nitrogen. An experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh, Bangladesh to evaluate the residual effects of different green manures on the growth and yield of wheat (BARI Gom-26). The experiment containing nine treatments were laid out in a randomized complete block design with three replications. The treatments were T1 [No green manure + 100% Recommended dose of nitrogen (RDN)], T2 (Sesbania aculeata + 75% RDN), T3 (Sesbania aculeata + 50% RDN), T4 (Sesbania rostrata + 75% RDN), T5 (Sesbania rostrata + 50% RDN), T6 (Vigna radiata + 75% RDN), T7 (Vigna radiata + 50% RDN), T8 (Vigna mungo + 75% RDN), and T9 (Vigna mungo + 50% RDN). Residual effects of green manures with RDN significantly increased the yield attributes as well as grain and straw yields of wheat. Further, green manures exerted significant residual effects on grain, straw and total N uptake of wheat. Among various treatments with green manures, the performance of T4 (Sesbania rostrata + 75% RDN) was the best as it produced the highest grain yield (4.28 t ha-1), straw yield (4.74 t ha-1) and total N uptake (108.02 kg ha-1). The use of green manures slightly increased the organic matter content, total N and available P, K, and S contents of the post-harvest soils. As regards to the contribution of various green manures on yield contributing characters and yield of wheat, performances of two Sesbania species viz., S. aculeata and S. rostrata in association with 75% N fertilizer were effective. Asian J. Med. Biol. Res. December 2016, 2(4): 624-630